AGRICULTURE AND CLIMATE CHANGE - Daniela Elena ȘURCĂ; Eduard Alexandru DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
At present, the most important anthropod pest of the maize in Europe is the European corn borer, Ostrinia nubilalis Hbn. In the infested areas, O. nubilalis is found with great frequency, starting from 20% in Hungary to 60% in Spain, and estimated production losses are between 5% and 30%, being considered as typical losses without too many control measures. Due to the major importance of this pest, between 2013 and 2016, at SCDA Turda the effect of some insecticides has been tested during the treatments on vegetation for corn borer control, under conditions of natural and artificial infestation with Ostrinia nubilalis. The most efficient role in the protection of maize culture, and implicitly of production, goes to the active substances indoxacarb and deltamethrine, in both infestation conditions, leading to very significant increase compared to the test counterpart. The least efficient results for corn borer control were obtained with the active substance thiacloprid.